Analysis Of The Quality Of Public Services In The Implementing Unit Of Population And Civil Registration In Cipayung Sub-District, East Jakarta - Soleh Harno; Khikmatul Islah (Social Science Studies, 2023)
The service of the Population and Civil Registration Implementation Unit of Cipayung Village, regardless of how good it is, does not necessarily have perfection. There are still shortcomings in the implementation process, and based on observations, problems are found that hinder the service process. This study uses qualitative methods that aim to analyze: (1) the quality of public services in the population and civil registration district in Cipayung Village; (2) supporting factors and obstacles to services in the population and civil registration district in Cipayung Village; and (3) efforts made in overcoming obstacles. Qualitative research is a study that aims to describe events and phenomena that occur in the field and present data systematically, factually, and accurately regarding the facts that occur in the field. The results of this study show that: (1) The quality of public services in the Population and Civil Registration Service in Cipayung Village has been applied to the dimensions of tangibleness, reliability, responsiveness, assurance, and emphaticness along with their indicators. However, it has not fully met the expectations of the community as users of the service. Among other things, the lack of friendly employees and the uncomfortable waiting room are lacking in meeting the criteria for indicators of the quality of public services in the Population and Civil Registration Satpel in Cipayung Village; (2) factors hindering the implementation of public services in the Population and Civil Registration Satpel in Cipayung Village are the lack of employee resources and dependence on one of the supporters of service infrastructure, namely the KTP stamp used for printing ID cards, which must wait from the central government; (3) the efforts made in overcoming obstacles are to ask for the help of officers in the village, provide training to each other's fellow employees, and always coordinate with related parties.